Galanin receptor 1 plays an antinociceptive effect via inhibiting PKA activation in the nucleus accumbens of rats with neuropathic pain - Zhang, Y; Gao, Y; Li, C-Y; Dong, W; Dong, Y; Li, M-N; Liu, Y-N; Xu, S-L (Physiological research, 2019)
Galanin and galanin receptors (GalRs) have been reported to be involved in the transmission and modulation of nociceptive information in the central nervous system (CNS). However, the underlying mechanism of the antinociception of GalRs in neuropathic pain remains unclear. This study investigated the antinociception induced by galanin receptor 1 (GalR1) via protein kinase A (PKA) signaling pathway in the nucleus accumbens (NAc) of rats with neuropathic pain. A mononeuropathy model was replicated by ligation of the left sciatic nerve, following which the expression of phospho-PKA (p-PKA) in the NAc were markedly up-regulated at 14(th) and 28(th) day after ligation of sciatic nerve, and p-PKA expression was down-regulated by intra-NAc injection of GalR1 agonist M617, but the GalR1 antagonist M35 did not have an effect. We also found that M35 in the NAc blocked the M617-induced increase in the hind paw withdrawal latencies (HWLs) of rats with mononeuropathy, but M35 alone had no effect on HWLs, and PKA inhibitor H-89 attenuated the M617-induced an increase in the HWLs. These results suggested that GalR1 induced an antinociception via inhibiting PKA activation, implying that GalR agonists may be potential and potent therapeutic options to treat chronic neuropathic pain.
Keywords: analgetika; Cyclic AMP-Dependent Protein Kinases; Pain Measurement; Galanin; Analgesics; nucleus accumbens; krysa rodu Rattus; zvířata; Enzyme Activation; neuralgie; Peptide Fragments; Neuralgia; potkani Sprague-Dawley; Bradykinin; Receptor, Galanin, Type 1; Male; peptidové fragmenty; bradykinin; Rats; receptor galaninu typ 1; Rats, Sprague-Dawley; proteinkinasy závislé na cyklickém AMP; Animals; aktivace enzymů; galanin; mužské pohlaví; Nucleus Accumbens; měření bolesti